FUTURE TEACHERS OF PHYSICAL EDUCATION THE SOCIAL-PEDAGOGICAL NEED OF DEVELOPING INTELLECTUAL CREATIVE COMPETENCE - Khabibullaev Ubaydulla (International Scientific and Current Research Conferences, 2022)
The reserve of qualified personnel prepared in the present period does not meet the modern demand of socio-economic systems. This situation, in turn, requires higher educational institutions to implement innovations in the personnel training system and labor market relations. The low level of intellectual competence of today's graduates is estimated by their inability to adapt to the situation, being limited only by theoretical knowledge, not being able to apply the acquired knowledge in practice, and not having a broad outlook and deep thinking. The socio-pedagogical necessity of developing the intellectual creative competence of future physical education teachers is scientifically analyzed in the article.